4CPS-131 Effectiveness of nusinersen in paediatric patients SMA1 and SMA2. (24th March 2020) - Ortenzi, GB; Palmas, G; Andresciani, E; Garzone, AMF; Berardi, MA; Siliquini, S; Porfiri, L; Demeo, MS; Guglielmi, S; Polidori, C; Pompilio, A
Abstract : Background and importance: Nusinersen is an innovative drug given by intrathecal injection and used to treat 5q-spinal muscular atrophy (SMA), a severe neuromuscular disorder due to a defect in the survival motor neuron 1 (SMN1) gene. This antisense oligonucleotide drug modifies RNA splicing of the SMN2 gene, thus increasing the production of full length SMN protein. The first dose, given as soon as possible after the diagnosis, should be followed by three more doses after 2, 4 and 9 (L1, L2, L3, L4) weeks and one dose every 4 months (M1, M2, M3...) thereafter. Aim and objectives: This study aims to describe the efficacy of nusinersen in terms of improvements in motor function in paediatric patients with SMA1 and SMA2. Material and methods: From February 2018, we collected data from 8 patients, 3 with SMA 1 and 5 with SMA 2, using specific neuromuscular functional tests: CHOP-INTEND, HINE and HFMSE Results: Results are expressed as points of increase (p) in motor function scores from baseline (or from the first score recorded in our centre* ) to the score obtained at the time of the last injection for each patient. SMA1 patients: 2 months old at the time of first injection (TFI): CHOP-INTEND 8/64 to +38p (M2); HINE 0/26 to +5p (M2). 3.3 years old TFI* : CHOP-INTEND 18/64 (M2) to +16p (M6); HINE 2/26, stable at M6. 5.6 years old TFI* : CHOP-INTEND 1/64 (M2) to −1p (M4); HINE 0/26 (M2) to +1p (M4), then suspended for absence of efficacy. SMA2 patients: 1.2 years old TFI: CHOP-INTEND 59/64 to −1p (M1). 3.4 years old TFI: CHOP-INTEND 41/64 to +8 (M1), +14p (M3); HFMSE 8/66 to stable at M1 +4p (M3). 4.6 years old TFI: CHOP-INTEND 55/64 to +6p (M1) +7 (M2); HFMSE 22/66 to +3p (M1), +3p (M3). 8.5 years old TFI: CHOP-INTEND 42/64 to +5p (M1); HFMSE 17/66 to +10p (M1). 11.5 years old TFI: CHOP-INTEND 37/64 to +2p (M1); HFMSE 8/66 stable at M1. Conclusion and relevance: Our results showed an average increase of 4 points for CHOP-INTEND and 3.75 points for HFMSE in SMA2 patients, after 6 months (M1) of treatment. For SMA1 patients, it was not possible to evaluate the average trend for CHOP-INTEND and HINE scores after 6 months of treatment because two patients started nusinersen in other hospitals (motor scores at L1–M1 not available). A longer follow-up and data from other parameters, such as swallowing and respiratory function, are important to better understand the overall efficacy of nusinersen. References and/or acknowledgements: No conflict of interest.